Non-isothermal cold crystallization kinetics of cork–polymer biocomposites based on polylactic acid for fused filament fabrication - Silva, S. P. Magalhães da (2020)
Cork–polymer composites (CPC) based on polylactic acid (PLA) matrix were prepared for the development of flaments for fused flament fabrication. The non-isothermal cold crystallization behaviours of PLA and CPC were investigated by diferential scanning calorimetry. Cold crystallization kinetic behaviours of PLA and CPC with 15 mass/% of cork powder residues at diferent heating rates (1.25, 2.5, 5 and 7.5 K min−1) were studied. Results showed that cold crystallization temperature (Tcc) of PLA matrix decreased with the addition of cork. Crystallization kinetic behaviour was studied by Avrami and Tobin models. It was shown that cork powder surface acts as a nucleating agent during non-isothermal cold crystallization, by accelerating the crystallization rate and, therefore, by reducing the half-time crystallization (t1/2) values. Polarized optical microscopy and X-ray difraction were used to evaluate the crystalline structure of PLA and CPC. Kissinger and Friedman methods were employed to determine the crystallization activation energy (Ec).